Sustaining China's Economic Growth in the Twenty-first. - Yao, Shujie (RoutledgeCurzon studies on the Chinese economy., 2003)
This book presents the work of a wide range of leading economists of China, who put forward new research findings and new thinking on a wide range of issues connected with the problem of sustaining China's economic growth.